PENGARUH MOTIVASI KERJA, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. AMDAFA MELANDU MANDIRI KECAMATAN LUBUK KILANGAN KOTA PADANG - Mahzum, Muhammad (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT UPI YPTK PADANG, 2019)
ABSTRACT This study aims to reveal, (1). The Influence of Intrinsic Motivation on Employee Performance, (2) Effect of Extrinsic Motivation on Employee Performance (3) Effect of Internationalized Employee Leadership Style on Employee Performance (4) Effect of anodizing Leadership Style Assignment on Employee Performance (5) Effect of Intrinsic & Extrinsic Motivation, alternative Style Employees & Tasks together on Employee Performance. The population in this study were employees of PT. Amdafa Guides Mandiri in Lubuk Kilangan Subdistrict, Padang City, amounting to 49 people. Sampling using Slovin formula and cluster random sampling method obtained a sample of 45 people. The method used in this research is simple random sampling method. The results of the study indicate that the variable Work Motivation and Leadership Style partially and simultaneously significantly influence Employee Performance   Keywords: Work Motivation, Leadership Style and Employee Performance